Solar and interplanetary disturbances - Alurkar, S. K (World Scientific, 1997)
Includes bibliographical references and index.; Solar and interplanetary propagating phenomena have been extensively studied during the last two decades. Very recently, a new simple model based on results from a density-mapping technique, pioneered at Cambridge, UK, has been proposed which overcomes the problems faced by the existing CME-driven shock theories. This monograph puts together those exciting developments in the field of solar and interplanetary dynamic phenomena with their effects, at times hazardous, on the terrestrial environment. It serves as an update and a ready reference for research students and scientists working in this field.